GREEN MARKETING: INNOVATIVE MANTRA OF MARKETING - Dr.M. VEERALAKSHMI (International Journal of Advanced Science and Technology, 2020)
The preservation and protection of our ecology pose a crucial challenge to business houses as well as to the society. It is believed that environmentalism will emerge as one of the critical issues that producers and marketers will need to integrate into their activities for successful operations and better results in the long run. Thus, concern over the environment has emerged as an important topic in the field of marketing. In the practice of marketing, the phrase ’green marketing’ has become quite popular. The conceptualizing of green marketing re-evaluates the very tenants of our consumption society. Without continued support from the physical environment, the means to satisfy the needs and wants of consumers will be curiously absent.